(untitled) (Community Based Medical Journal, 2022)
Introduction: Dry eye is a multifactorial disease of the tears and ocular surface, is highly prevalent and has a significant impact on quality of life. Long term use of Cyclosporine has demonstrated that this drug halt progression of chronic dry eye disease and is associated with a cure of signs and symptoms of Dry Eye disease. The aim of our study is to evaluate the efficacy of topical Cyclosporine A (0˙05%) for the treatment of mild, moderate and severe dry eye disease. Methods: This prospective study was conducted in the ophthalmology department of Combined Military Hospital, Jashore from January 2019 to December 2019 among selected 20 patients aged 20-26 years with a confirmed diagnosis of dry eye syndrome refractory to conventional management. All the patients were treated with Cyclosporine A twice daily and were evaluated at month 1,2,3,4,5 and 6 for changes from base line in tear film break up time, schirmer test, fluorescein staining, tear meniscus height, symptoms of ocular discomfort and visual acuity. Result: Mean age of 20 cases was 48.7 years among them 14(70%) female and 6(30%) male. Mean TBUT improved from 4.4 second to 8.7 second (p=0.001) after 6 months of treatment. SCHIRMERʼS paper test was performed before the beginning of the treatment and showed improvement of wetting from mean 3.5mm to 8.2mm (p=0.001) after 6 month. Mean lower tear meniscus height improved from 0.2 mm to 0.63 mm (p=0.002) after 6 months of treatment. Fluorescein staining was significantly lowered from mean 2.8 to 1.8 (p=0.001) with significant reduction of ocular symptoms and improvement of visual acuity after 6 months of treatment. Conclusion: Topical Cyclosporine A (0˙05%) has been demonstrated to be effective in all categories of dry eye disease. It reduces symptoms and signs of dry eye disease with the greatest improvement of signs in patients with severe dry eye disease. CBMJ 2021 January: vol. 10 no. 02 P: 98-104